TARGHIB WA TARHIB LEARNING METHOD IN RELIGIOUS EDUCATION CLASSROOM MANAGEMENT - Mastur Thoyib (PT. Intelek Cendikiawan Nusantara, 2025)
The Targhib wa Tarhib method plays an important role in Islamic religious education to shape the character of students. Targhib refers to providing positive motivation, while Tarhib involves warning or threatening to prevent negative behavior. Using literature review approach, this study describes the application and effectiveness of this method in learning, combining the principles of Islamic education and motivation to improve students' morals. The Targhib wa Tarhib method aims to build moral awareness and responsibility, with strategic application that takes into account teachers' understanding and educational conditions. This approach has the advantage of motivating students to do good, but it also faces challenges in its implementation. This study uses a literature research method to examine the implementation and impact of the method, referring to the teachings of the Qur'an and Hadith as well as related literature.